Karakteristik Pedoagroklimat untuk Pengembangan Perkebunan Karet dan Kelapa Sawit di Wilayah Moramo Sulawesi Tenggara - Syamsu Alam; Sahta Ginting; M Tufaila Hemon; Aliyaman Aliyaman; Jufri Karim; Anna Kusumawati (Fakultas Pertanian, Universitas Timor, 2023)
Information on land characteristics, especially climatic and soil conditions of an area, is not only needed in determining land suitability but also in determining alternative management inputs needed for the development of certain commodities, including rubber and oil palm. Rubber and oil palm are export commodities that are national priority whose productivity continues to be pursued, including through extensification to various regions. This study aims to determine the potential for the development of rubber and oil palm plantations in Moramo and surrounding areas, based on soil and climatic conditions. Soil survey method which aims to obtain land characteristics data is used in this study. The characteristics of the land observed were climatic conditions such as temperature, rainfall, and dry months, and soil conditions such as drainage, texture, effective depth, cation exchange capacity, base saturation, pH, C-organic, P2O5, K2O, surface rocks, erosion hazard, slopes, and flood hazards. Evaluation of land suitability was carried out using the matching method between land characteristic data obtained from the field and laboratory with the criteria for growing rubber and oil palm plantations. The results showed that the climatic conditions that could be a limiting factor for the development of rubber and oil palm plantations in the Moramo area were rainfall and air temperature. Soil conditions that are limiting factors for the development of rubber and oil palm plantations in the Moramo area can be in the form of effective soil depth, slope, and erosion hazards. Management inputs that need to be carried out for the development of rubber and oil palm plantations in the Moramo area are soil conservation measures for erosion and slope limiting factors, and irrigation system settings for rainfall limiting factors. Potentially based on climate and soil conditions, rubber and oil palm plantations have the potential to be developed in most areas of Moramo.